"From resistance to challenge": child health service nurses experiences of how a course in group leadership affected their management of parental groups - Åsa Lefèvre; Pia Lundqvist; Eva Drevenhorn; Inger Hallström (BMC, 2017)
Abstract Background All parents in Sweden are invited to child health service (CHS) parental groups, however only 49% of the families participate. The way the parental groups are managed has been shown to be of importance for how parents experience the support and CHS nurses describe feeling insecure when running the groups. Lack of facilitation, structure and leadership might jeopardise the potential benefit of such support groups. This study describes CHS nurses' experiences of how a course in group leadership affected the way they ran their parental groups. Methods A course in group leadership given to 56 CHS nurses was evaluated in focus group interviews 5-8 months after the course. Results The nurses felt strengthened in their group leader role and changed their leadership methods. The management of parental groups was after the course perceived as an important work task and the nurses included time for planning, preparation and evaluation, which they felt improved their parental groups. Parental participation in the activities in the group had become a key issue and they used their new exercises and tools to increase this. They expressed feeling more confident and relaxed in their role as group leaders and felt that they could adapt their leadership to the needs of the parents. Conclusions Specific training might strengthen the CHS nurses in their group leader role and give them new motivation to fulfil their work with parental groups. Trial registration  Clinical Trials.gov ID: NCT02494128 .